Instrumental and Political Explanations in the Implementation of Various Prison Public-Private Partnership (PPP) Models - Aisyah, Sani Siti; Meliala, Adrianus; Sulhin, Iqrak (Transpublika Publisher, 2024)
This study highlights that the practice of Public-Private Partnership (PPP) in prison, based on the experiences of various countries such as the United States, England, Australia, France, Japan, and Canada, does not have a single pattern. The diversity of PPP practice patterns in prison is identified by this study in various prison PPP models consisting of: 1) the